Penerapan Algoritma Dijkstra Pada Game Learning Matematika Berbasis Android - John Adler; Bagas Farid Ramadhan (Komputika : Jurnal Sistem Komputer, 2021)
ABSTRACT – A survey institute in the field of gaming. Newzoo ranks Indonesia 16th in the world in terms of game usage that is in high demand by the productive age range of 10-20 years. To consider the need for learning and educational processes for games so that children at this age will not like games that will damage brain cells. Therefore by building and supporting maze games that have excellent educational value for children, then using the Dijkstra algorithm, as an artificial intelligence system to find the fastest way to get to a location. Which will train children's brains to think and develop so that children are not dependent anymore on destructive games. By using the black box method, it can be concluded that 18 children from the range of grade 5 to grade 1 of junior high who play this game 88.9% agree this game is in accordance with the material they intended, then this game is also fun and they want to play it again . This meaningful game can be used as an alternative to school learning. Keywords – Dijkstra algorithm; Maze Game; Artificial Intelligence; Android; Mathematics Learning.